SISTEM REKOMENDASI BUKU PADA APLIKASI PERPUSTAKAAN MENGGUNAKAN METODE COLLABORATIVE FILTERING PADA SMKN 1 BANGIL - Abdul Rokhim; Akhmad Saikhu (SPIRIT, 2017)
Recommender system aims to predict the likelihood of books interest or useful for students . This study describes the making of a recommendation system that is able to automatically make a recommendation to the students . Recommendations are shown to students in the form of a list of books that have been sorted prediction results of the greatest equality of outcome prediction . In applications made , the recommendations given to the students there are two kinds, namely recommendation filtering demographic used for students who have not borrowed books , recommendations are given based on the similarity between the profiles of students Keyword: Library, Recommendation System, Collaborative Filtering.Keyword: Library, Recommendation System, Collaborative Filtering.